Komposisi dan Kekuatan Tekan Beton Karakteristik pada Campuran Semen Nusantara, Pasir dan Split dari Beberapa Tempat di Sekitar Kabupaten Banyumas - Gandadinata, Indrayana (Department of Civil Engineering, Diponegoro University, 2004)
As usually the composition/formation for concrete mixing there has 1 part of cement : 2 parts of sand : 3 parts of crushing stone (1:2:3) or 1 part of cement : 1,5 parts of sand : 2,5 parts of crushing stone (1:1,5:2,5) to be reckoned and also usually doing in Banyumas Regency. In spite of this case to make problems: (i) if the composition/formation for concrete mixing as above has usually already exactly use for base material/raw material condition like sand and crushing stone to be in stock in several places round about Banyumas Regency; (ii) when is’nt it, therefore how much the composition/formation for concrete mixing exactly good based to the base material/raw material condition to be in stock in several places round about Banyumas Regency; and (iii) when the composition/formation for concrete mixing is exactly/good to be able to known and after that how many strong of the characteristic compression can be reach by several composition/formation for concrete mixing use the material to be come from several places round about Banyumas Regency as above mentioned. The problems as above mentioned to be important to examined because with the condition of base material/raw material to be in stock suppose that the concrete mixing composition not as usually, this case must be important to prove because Banyumas Region and round about it has many base material/raw material but not yet efficiency use with the exactly composition. From the result of examination which to execute in laboratory based on sive analysis and concrete cube test (crushing test) determined the concrete mixing composition for the materials to be in stock from several places round about Banyumas Regency, there was 1 part of cement : 2 parts of sand : 2 parts of crushing stone (1:2:2) not as usually and the concrete characteristic compression (sbk) was about between 181,50 kg/cm2 – 242,53 kg/cm2.Keywords: Concrete Composition, Concrete Characteristic CompressionPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3890[How to cite: Gandadinata, I., 2004, Komposisi dan Kekuatan Tekan Beton Karakteristik pada Campuran Semen Nusantara, Pasir dan Split dari Beberapa Tempat di Sekitar Kabupaten Banyumas, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 84-90]